CEO communication: engagement, longevity and founder centrality: An exploratory study in Italy. (7th August 2017) - Conte, Francesca; Siano, Alfonso; Vollero, Agostino
Abstract : Purpose: The purpose of this paper is to analyse the engagement of chief executive officers (CEOs) in corporate communication and focus on how their approach to communication develops in relation to the longevity of their tenure. The paper also explores how founder centrality is linked to the objectives of CEO communication and the CEOs' use of personal social media. Design/methodology/approach: The paper brings together the relevant literature from different disciplines, related to leadership communication, CEO longevity and founder centrality, and reveals a number of unexplored issues. Four research questions were defined and an exploratory survey was carried out, involving 93 CEOs from large companies located in Italy. Findings: The results show that CEOs are strongly engaged in institutional communication. Short-tenured CEOs seem more engaged in building and consolidating relationship networks with specific stakeholders (customers and employees), while long-tenured CEOs tend to be more involved in institutional and financial communications. Research limitations/implications: Due to the exploratory research design and the circumscribed sample from a single country (Italy), further cross-national evidence is needed to substantiate the suggested links between engagement in communication activities and longevity. The study highlights the managerial and communication skills that CEOs must be provided with during their corporate tenure, thus suggesting the need to further examine the "life cycle" of CEO communication activities. Originality/value: The paper sheds light on CEO communication dynamics. It is the first of its kind in the Italian context, where some factors, such as longevity of tenure, seem to play an important role in shaping corporate communication objectives and activities.